Dynamic correlation among title transfer facility natural gas, Brent oil and electricity EPEX spot markets: Spillover effects of economic shocks on returns and volatility - Gustavo Soutinho; Vítor Miguel Ribeiro; Isabel Soares (AIMS Energy, 2023)
This research explores the spillover effects in the directional movement of returns and the persistence of shocks among three prominent energy spot markets: b transfer facility for natural gas, Brent crude oil and electricity markets from monthly price data spanning January 2010 to September 2022. Methodologically, we initially employ bivariate vector autoregressive models to detect potential lagged return effects from one spot market on another. Then, we examine the impact on the conditional mean returns and volatility across these spot markets using the standard dynamic conditional correlation (DCC) model, as well as the respective asymmetric (ADCC) and flexible (FDCC) extensions. In addition, we accommodate innovative insights that include recent datasets on the COVID-19 crisis and the Ukrainian war, which constitute a new addition to the existent literature. The empirical findings confirm the significant impact of these two unprecedented moments of contemporaneous history, given that both events are substantiated by an exponential increase in prices and by a rise in volatility. However, the effect on returns was not uniform across the time series. Specifically, there was a consistent increase in volatility for natural gas and electricity from the start of 2020 until the end of 2022, while Brent oil exhibited a substantial peak only in the first half of 2020. This study also reveals that previous lagged returns within each market, particularly for Brent oil and electricity, had statistically significant effects on current returns. There was also a robust unidirectional positive spillover effect from the Brent oil market to the returns of electricity and the natural gas markets. The study also reveals the presence of a weak positive autocorrelation between natural gas and electricity returns, and positive shocks to returns had a more pronounced impact on volatility compared to negative shocks across all the time series.